Cross-Cultural Understanding dan Deradikalisasi Agama: Studi Kasus Mahasiswa Pendidikan Bahasa Inggris IAIN Surakarta - Tyas Mulyono; Arif Rifanan; Sarah Muktiati; Dina Fitri Annisa; Tri Yulianingsih (Academica: Journal of Multidisciplinary Studies, 2017)
This article aims to determine the role of subjects Cross-Cultural Understanding in an effort de-radicalization among students majoring inÂ English and optimize it to protect students from the influence of radical Islam. The collection of data carried out by interviewing several CCU lecturers in Islamic Education and Teacher Training Faculty IAIN Surakarta and distributing questionnaires to English Education students using Google Drive. Interviews indicate that this course has a close relationship with efforts to de-radicalization of Islam. As the results of the questionnaire indicate that 69.8% of students answered strongly agree Cross-Cultural Understanding courses teach to tolerate as an effort to reduce radical movements, hereby this course can be used by English educators to contribute in efforts to the de-radicalization program.Keywords:Cross-cultural understanding, Islamic radicalism, De-radicalization